Introduction to the WTO Agreement - Das, Bhagirath Lal (New Delhi, 2007)
This book, by an author who was intimately involved in the Uruguay Round which led to the creation of the WTO, is an indispensable and concise explanation of what the WTO Agreements actually provide for. It deals with the full range of technical provisions and issues, explaining where necessary the background, terms involved, and implications of the new provisions.
Keywords: WTO Agreement